MAXIMIZING THE POTENTIAL OF TECHNOLOGY FOR RELIGIOUS LEARNING IN MADRASAH - Firmansyah; Nur Faiz Habibah; A., Hamid (CV. ADIBA ASIHA AMIRA, 2024)
The research aims to analyze and synthesize the various literature available on the application of learning technology in the context of religious education in madrasah. The use of learning technology, including digital media, online learning platforms, interactive educational tools, and virtual teaching, has been seen as a key factor in enriching the religious learning process. The study uses a method of literary research, in which data is collected through a systematic review of books, journal articles, research reports, and relevant digital sources. Research results show that the application of technology in religious learning in the madrasah offers a number of benefits, including improved accessibility of learning materials, personalization of learning, improved interaction and collaboration, and more interesting and effective learning. Studies of literature also reveal challenges such as lack of adequate infrastructure, lack of technical training for teachers, and issues related to learning content that matches religious values. The study recommends strategies to address these challenges, which include investment in technological infrastructures, training and professional development of teachers and the development and evaluation of creative and innovative learning content whileining religious value. Integrating creative and effective learning technologies into religious education in madrasah indeed requires sustained and collaborative efforts among educational stakeholders. Through the wise introduction of technology, religious education can become more relevant, interesting, and meaningful for students in the ever-changing digital age.